The Effect of Health Education Through Video on Girls Knowledge with Visual and Hearing Impairments About Sexually Transmitted Infections - Latifah, Ulfa; Handayani, Dini Saraswati; Elba, Fardila; Susanti, Ari Indra; Martini, Neneng (The Center for Disability Studies and Services Brawijaya University, 2021)
Girls with disabilities are more at risk of contracting STIs because they are a vulnerable group, lacking information and reproductive health services so that hygiene is not well maintained. This study aimed to determine the effect of health education through a video about STIs on the knowledge of girls who were blind and deaf in Bandung City. This study used a pre-experimental method with one group pretest-posttest design in October-December 2019. The research sample was girls who were blind and deaf at Extraordinary Schools in Bandung City. The sampling technique was total sampling with 63 respondents. Data collection was carried out by interviews and questionnaire. Bivariate data analysis used Paired T-Test. In this study, there was an effect of health education through video on the knowledge of girls who were blind and deaf about STIs.